(3GdbhGYO aj GdChbGJs - (3YHO Gddg Hf CMeO GdefGhj GdTGaYj,J (B1060 (3g` s
(3ChdgG (B:s
(3GdMeO ddg YGdi GdMeO hGdTCf dGjfbV HGfbVGA MbH hCReGf s
(3BNQgG (B:s
(3hdG NjQ ajef cGf HGdhbJ LGgdkG hde jc PG Yde HeG jJYHO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B42 - (3U(B48s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B21s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B81 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B181) s
Keywords: (3Gdadcs